The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5483/bmbrep.2012.45.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid treatment independently affects expansion and transdifferentiation of porcine neonatal pancreas cell clusters

Abstract: The purpose of this study was to determine the effects of duration and timing of glucocorticoid treatment on the expansion and differentiation of porcine neonatal pancreas cell clusters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We suggest that PGC-1α plays a similar role in the GR-mediated repression of Pdx1 in β-cells. In line with this, a recent article showed that GCs treatment decreased Pdx1, increased PGC-1α expression, and inhibited porcine neonatal pancreas cell cluster differentiation into β-cells (41). Thus, similarly to what we show in murine fetal pancreas, PGC-1α is stimulated by GCs in porcine cells.…”
Section: Discussionmentioning
confidence: 63%
“…We suggest that PGC-1α plays a similar role in the GR-mediated repression of Pdx1 in β-cells. In line with this, a recent article showed that GCs treatment decreased Pdx1, increased PGC-1α expression, and inhibited porcine neonatal pancreas cell cluster differentiation into β-cells (41). Thus, similarly to what we show in murine fetal pancreas, PGC-1α is stimulated by GCs in porcine cells.…”
Section: Discussionmentioning
confidence: 63%
“…UCP-2 is expressed under conditions driving mitochondrial dysfunction, including hyperglycemia, and reduces the mitochondrial membrane potential when the electron flow cannot be coupled to ATP synthesis. PGC-1α overexpression may also inhibit β-cell differentiation [49,50]. However, human genetic studies suggest a protective role of PGC-1α in DM [51].…”
Section: Diabetesmentioning
confidence: 99%
“…Recent studies in rodents have demonstrated that Dx suppresses the expansion and differentiation of transplanted NPCCs (18). This impairment of A-cell differentiation seemed to be mediated by pancreatic transcription factors, which might be related to the expression of PGC-1> upon Dx treatment (24). In vivo experiments clearly indicated that the expression of insulin in the graft tissue disappeared in the Dx-injected group, but the siPGC-1>-and Dx-treated group showed strong insulin expression in the graft.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, reported studies using a glucocorticoid receptorinactivation model suggested that an excess of glucocorticoid impairs the differentiation of the A-cell lineage exclusively in the pancreas (21Y23). We previously reported that Dx treatment remarkably suppressed graft mass expansion at an early stage after transplantation, and the endocrine differentiation of porcine NPCCs was correlated with the duration of Dx treatment (24). This impairment of A-cell differentiation seemed to be mediated by pancreatic transcription factors, which may play a role in the expression of PGC-1> after treatment with Dx.…”
mentioning
confidence: 97%